Dietary Modulation of Oxidative Stress From Edible Insects: A Mini-Review - D'Antonio, Veronica; Serafini, Mauro; Battista, Natalia (Frontiers in Nutrition, 2021)
Edible insects are proposed as a nutritious and environmentally sustainable alternative source to animal proteins, due to their numerous advantages in terms of reduced ecological impact and high nutritional value. However, the novelty for edible insect rely on the content of bioactive ingredients potentially able to induce a functional effect in the body. However, a review of the evidences about this aspect is still lacking. The present work aim to review the research findings on the antioxidant properties of edible insects available in the literature. A total of twenty-five studies involving animals, cell cultures or in vitro experimental studies evaluating the antioxidant effect of edible insects are presented in this work. When the antioxidant activity was investigated, using a wide variety of in vitro tests and in cellular models, positive results were shown. Dietary supplementation with edible insects was also able to counteract dietary oxidative stress in animal models, restoring the balance of antioxidant enzymes and reducing the formation of oxidation damage markers. On the basis of the reviewed evidences, edible insects might represent a source of novel redox ingredients at low ecological impact able to modulate oxidative stress. However, due to the fact that majority of these evidences have been obtained in vitro, cellular and in animal models, dietary intervention trials are needed to assess the efficacy of edible insect consumption to modulate redox status in humans.